A Complex Renal Cyst: It Is Time to Call the Oncologist?. (10th May 2011) - Granata, Antonio; Basile, Antonio; Bruno, Giuseppe Alessandro; Saita, Alberto; Falsaperla, Mario; Figuera, Michele; Gallieni, Maurizio; Floccari, Fulvio
Abstract : Introduction . Hydatid disease is a cyclozoonotic parasitic infestation caused by the cestode Echinococcus granulosus . The cysts mainly arise in the liver (50 to 70%) or lung (20 to 30%), but any other organ can be involved, in abdominal and pelvic locations, as well as in other less common sites, which may make both diagnosis and treatment more complex. Isolated renal involvement is extremely rare. Case Presentation . We report a rare case of isolated renal hydatid disease in a 71-year-old man with a history of vague abdominal pain, anemia, fever, and microhematuria. Ultrasonographic examination revealed a complex cyst in the right kidney, including multiple smaller cysts with internal echoes. A magnetic resonance scan of the abdomen confirmed the findings, and hydatid cyst disease was diagnosed. Right nephrectomy was performed, and microscopic examination confirmed the diagnosis of hydatid cyst. Albendazole, 10 mg/kg per day, was given for 4 weeks (2 weeks preoperatively and 2 weeks postoperatively). Conclusion . Isolated primary hydatidosis of the kidney should always be considered in the differential diagnosis of any cystic renal mass, even in the absence of accompanying involvement of liver or other visceral organs.